The microbial nitrogen cycle - Marlene Mark Jensen (Frontiers Research Topics, 2015)
Nitrogen is an essential element in biological systems, and one that often limits production in both aquatic and terrestrial systems. Due to its requirement in biological macromolecules, its acquisition and cycling have the potential to structure microbial communities, as well as to control productivity on the ecosystem scale. In addition, its versatile redox chemistry is the basis of complex biogeochemical transformations that control the inventory of fixed nitrogen, both in local environments and over geological time. Although many of the pathways in the microbial nitrogen cycle were described more than a century ago, additional fundamental pathways have been discovered only recently. These findings imply that we still have much to learn about the microbial nitrogen cycle, the organisms responsible for it, and their interactions in natural and human environments. Progress in nitrogen cycle research has been facilitated by recent rapid technological advances, especially in genomics and isotopic approaches. In this Research Topic, we reviewed the leading edge of nitrogen cycle research based on these approaches, as well as by exploring microbial processes in modern ecosystems.